PREVALENCE OF ANEMIA, IRON DEFICIENCY, AND IRON DEFICIENCY ANEMIA AND DIAGNOSTIC PERFORMANCE OF HEMATOLOGIC AND BIOCHEMICAL MARKERS OF SIDEROPENIA IN 1- TO 5-YEAR-OLD CHILDREN IN THRACE GREECE - Panagiota Zikidou; Christina Tsigalou; Gregorios Trypsianis; Alexandros Karvelas; Aggelos Tsalkidis; Elpis Mantadakis (Mediterranean Journal of Hematology and Infectious Diseases)
Background and Objectives: Iron deficiency (ID) is a major public health problem with high prevalence in early childhood. We assessed the prevalence of anemia, ID, and iron deficiency anemia (IDA) in healthy children of Thrace, Greece, its correlation with dietary factors, and evaluated the diagnostic performance of hematologic and biochemical markers of sideropenia.